ANTHROPOMETRY OF THE EXTERNAL EAR AMONG ADULT IJAWS IN BAYELSA STATE OF NIGERIA - Edibamode, E. I.; Mordi, K.; David, L. K.; Eghoi, A. M. (International Journal of Medicine and Medical Research, 2019)
Background. External ear measurement is of utmost importance in reconstructive surgeries. Objectives. The present study is aimed at ascertaining sexual dimorphism in external ear anthropometry and ear lobe attachments among adults Ijaws in Bayelsa, Nigeria. Methods. A total of 112 adults within the age range of 18-50 yrs, who met the inclusion criteria, were involved in the study. Four linear dimensions of the ear, which are ear length (EL), ear width (EW), lobular length (LL) and lobular width (LW), were measured for both genders. The lobular attachment for both ears for males and females were also examined and results recorded. These data were subjected to Student t-test, Chi-square test, and Pearson’s correlation using SPSS version 20.0. Results. The mean values for EL, EW, LL, and LW for the left auricle in the males and females were 58.14±0.60, 27.41±0.37, 14.47±0.27, 13.50±0.34 and 57.90±0.16, 27.45±0.65, 15.41±0.31, 13.43±0.38 respectively. However, for the right auricle in the males and females, the values were 58.40±0.45, 28.21±0.68, 14.32±0.31, 13.04±0.32, and 56.66±1.10, 27.51±0.65, 15.58±0.29, 13.28±0.34 respectively. The left and right lobular length were the only parameters that proved statistical significance (p<0.05) in females compare to males. Pearson’s correlations between right and left sides for each of the parameters were positive and significant. Chi-square analysis revealed no significant relationship (p>0.05) between earlobe attachments and gender. Conclusions. Sexual dimorphism was thus established in the Ijaw population as regards lobular length dimensions. It is believed that the results of this study would be very useful for ear morphology and reconstructive surgeries.